2015
DOI: 10.1111/1467-8551.12156
|View full text |Cite
|
Sign up to set email alerts
|

Look What's Back! Institutional Complexity, Reversibility and the Knotting of Logics

Abstract: Through a comparative historical study of community pharmacy in the UK, Italy, Sweden and the USA, we examine what happens to institutional arrangements designed to resolve ongoing conflicts between institutional logics over extended periods of time. We find that institutional arrangements can reflect the heterogeneity of multiple logics without resulting in hybridization or dominance. Because logics remain active, similar conflicts can reappear multiple times. We find that the durability of the configurations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 47 publications
(54 reference statements)
0
41
0
1
Order By: Relevance
“…Institutional logics provide the common rules that govern organisational action in a given institutional environment (Hughes, Powell, Chung & Mellahi, 2017;Kasper & Streit, 1998;Nicolini, Delmestri, Goodrick, Reay, Lindberg & Adolfsson, 2016;Thornton 2004). Greenwood, Díaz, Li, and Lorente (2010, p. 521) argue that "organizational forms and managerial practices are manifestations of, and legitimated by, institutional logics".…”
Section: Social Identity Theory and Market And Institutional Logicsmentioning
confidence: 99%
“…Institutional logics provide the common rules that govern organisational action in a given institutional environment (Hughes, Powell, Chung & Mellahi, 2017;Kasper & Streit, 1998;Nicolini, Delmestri, Goodrick, Reay, Lindberg & Adolfsson, 2016;Thornton 2004). Greenwood, Díaz, Li, and Lorente (2010, p. 521) argue that "organizational forms and managerial practices are manifestations of, and legitimated by, institutional logics".…”
Section: Social Identity Theory and Market And Institutional Logicsmentioning
confidence: 99%
“…In literature we can find different ways of conceptualizing the relationship between multiple logics (Reay et al, 2009, Westenholz, 2011Nicolini et al, 2016). Some authors argue that among logics there is a dominant one which guides behaviours and in this conceptualization, different institutional logics coexist within an organizational field, challenging each other to become dominant and pushing for radical or incremental changes.…”
Section: Theoretical Background: Institutional Logics In the Organizamentioning
confidence: 99%
“…12, No. 8;2017 The research carried out on the field of TWAs has highlighted the importance of events to understand the development process of the organizational fields and interdependence between logics and action (Meyer, Brooks, & Goes,1990;Greenwood, Suddaby, & Hinings, 2002;Nicolini et al, 2016). The analysis shows the existence of a series of inconsequential events that, nevertheless, represent significant moments in the evolution of the field under investigation and confirm the existence of an institutional logic in a certain period.…”
Section: Evolution Of Twas Field: the Main Eventsmentioning
confidence: 99%
“…Whereas early work about logic multiplicity framed the relationship between conflicting logics in terms of dominance (Nicolini, Delmestri, Goodrick, Reay, Lindberg, & Adolfsson, 2016), as if one logic won, later research associated logic multiplicity with increased durability, sustainability, and innovativeness (Besharov & Smith, 2014). Additionally, research found that multiple conflicting logics can coexist for long periods of time or remain unresolved (Nicolini et al, 2016), and organisations that could not achieve their goals with one singular logic were identified (Johansen & Waldorff, 2015).…”
Section: Multiplicity Of Logicsmentioning
confidence: 99%
“…Whereas early work about logic multiplicity framed the relationship between conflicting logics in terms of dominance (Nicolini, Delmestri, Goodrick, Reay, Lindberg, & Adolfsson, 2016), as if one logic won, later research associated logic multiplicity with increased durability, sustainability, and innovativeness (Besharov & Smith, 2014). Additionally, research found that multiple conflicting logics can coexist for long periods of time or remain unresolved (Nicolini et al, 2016), and organisations that could not achieve their goals with one singular logic were identified (Johansen & Waldorff, 2015). In order to account for these conflicting outcomes of logic multiplicity research, Besharov and Smith (2014) developed a framework that allows for the categorisation of organisations along two (continues) axes: the degree of logic compatibility (i.e., the extent to which logics provide (in)compatible prescriptions for action) and the degree of logic centrality (i.e., the extent to which one or multiple logics are core to organisational functioning).…”
Section: Multiplicity Of Logicsmentioning
confidence: 99%